(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The impact of gaming on cognitive development and attentional abilities are the primary foci of this study, which also examines the relationship between gaming and learning outcomes. The potential of video games to improve attentional control, cognitive flexibility, and learning—all of which could lead to novel approaches to treating developmental disorders—is discussed here. It would appear that video games, which were originally created for entertainment purposes, improve behaviour in areas as diverse as perception, attention, mental rotation, and task switching. A better signal-to-noise ratio and, by extension, better decisions, may be made possible by this unexpectedly extensive transfer, which is facilitated by improved attentional regulation. Computerised training or self-regulation approaches are two examples of targeted interventions that have the potential to improve attentional control. The incredible amount of time that people all over the globe spend with this medium makes the idea of incorporating such training into video game play all the more enticing. It has the potential to improve the utilisation of positive effect games, which in turn could increase patient compliance and student motivation. This work can be further developed and its impact on developmental diseases can be addressed by utilising computational models from developmental robotics or machine learning, which offer a rich theoretical foundation.